Implementasi Sistem Informasi Penggajian Digital Berbasis Java-MySQL untuk Optimalisasi Administrasi Tenaga Honorer: Studi Kasus Dinas Perdagangan Kabupaten Nabire - Eka Melani Majid; Gunawan Prayitno (STMIK Pesat Nabire, 2025)
The manual payroll process for honorary staff at the Department of Trade of Nabire Regency often leads to calculation errors and administrative delays, affecting employee satisfaction. This study aims to develop a more efficient and accurate payroll information system. The system is designed using the Java programming language and MySQL database, following the Waterfall development method. Through requirements analysis, design, implementation, testing, and evaluation, the system has been developed to improve the accuracy and effectiveness of the payroll process. Test results show that the system successfully reduces calculation errors by up to 90% and shortens the payroll processing time. Therefore, this system is expected to be a practical solution for the Department of Trade to manage honorary staff payments more effectively.